2016
DOI: 10.1089/tmj.2015.0235
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible and Integrated System for the Remote Acquisition of Neuropsychological Data in Stroke Research

Abstract: Background: Neuropsychological testing is a central aspect of stroke research because it provides critical information about the cognitive-behavioral status of stroke survivors, as well as the diagnosis and treatment of stroke-related disorders. Standard neuropsychological methods rely upon face-to-face interactions between a patient and researcher, which creates geographic and logistical barriers that impede research progress and treatment advances. Introduction: To overcome these barriers, we created a flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…Videoconferencing has been shown to be reliable not only in AD, but to assess the cognitive functions in other pathologies. Interesting results were provided for psychiatric patients [ 32 - 33 ], patients with Parkinson disease [ 34 ], and stroke patients [ 35 ], as well as in older adults [ 36 ]. Furthermore, videoconferencing has been found useful to evaluate the clinical status [ 37 ] and rehabilitation [ 38 ] of patients affected by different neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Videoconferencing has been shown to be reliable not only in AD, but to assess the cognitive functions in other pathologies. Interesting results were provided for psychiatric patients [ 32 - 33 ], patients with Parkinson disease [ 34 ], and stroke patients [ 35 ], as well as in older adults [ 36 ]. Furthermore, videoconferencing has been found useful to evaluate the clinical status [ 37 ] and rehabilitation [ 38 ] of patients affected by different neurological disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 30 studies on the computer-based cognitive assessment of stroke patients were identified. Of these, 21 studies on cognitive assessment tools focusing on evaluating multi-domain or global cognition featured the following tools: Computerized Activity Measure for Post-Acute Care (AM-PAC) ( 24 , 25 ), NeuroTrax™ (also known as MindStreams ® ) ( 26 29 ), NIH Toolbox Cognition Battery (NIHTB-CB) ( 30 32 ), CogState Battery (CogState Ltd., Australia) ( 33 , 34 ), Seoul Computerized Neuropsychological Test (SCNT, Maxmedica Inc.) ( 35 37 ), computerized shape cancellation task ( 38 , 39 ), computerized touchscreen cancellation, sustained attention and spatial working memory ( 40 ), computerized test of Attention Performance, Delis-Kaplan Executive Function System and Tower of London ( 41 ), Ryokansan touch panel-type screening test ( 42 ), Intelligent Cognitive Assessment System (ICAS) ( 43 ), and remote acquisition of neuropsychological data (RAND) ( 44 ). Meanwhile, nine studies reported tools for the assessment of cognition for a single domain, including computerized visual search task ( 45 , 46 ), the PC test Amunet (NeuroScios GmbH, Austria) ( 47 ), computerized Wisconsin Card Sorting Test ( 48 ), computerized Iowa Gambling Task (IGT) ( 49 ), Tablet-based Symbol Digit Modalities Test (T-SDMT) ( 50 ), computer adaptive testing in Neuro-QOL ( 51 ), auditory test of variables of attention (TOVA) ( 52 ), and computer-based visuomotor task ( 53 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Besides, robot-based CCA could provide support for patients' limbs to reduce fatigue ( 18 ). Meanwhile, Durisko et al ( 44 ) emphasized the feasibility of using RAND system for virtual home-based assessment without prior face-to-face contact between a participant and researcher. Wallmark et al ( 52 ) suggested that the auditory versions of such tools could avoid the possible risk of epileptic seizures in patients exposed to flashing screens.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed solution contributes to the growing need for person-centered home-care technologies [42], comparable to similar applications in other contexts [43]. To ascertain whether the generalization of perceptual learning might occur using an adaptive framework, a larger sample is necessary, together with the evaluation of independent functional measures pre-and post-training.…”
Section: Future Perspectivementioning
confidence: 99%